The role of frozen section evaluation in the diagnosis of adnexal mass. Issue 2 (1st February 2008) - Taskiran, C.; Erdem, O.; Onan, A.; Bozkurt, N.; Yaman-Tunc, S.; Ataoglu, O.; Guner, H.
Abstract : The purpose of this study was to evaluate the accuracy of frozen section diagnosis in patients who were subjected to the exploratory laparotomy for pelvic mass. Overall, 207 patients were included in this study and the mean age of the patients was 50.9 ± 14.9 years (range, 18–84 years). Of these patients, 98 (47%) had benign, 16 (8%) had borderline, and 93 (45%) had malignant histologies at permanent section. The diagnosis at frozen section was deferred for three patients (1.4%) and these patients were excluded from the further analyses. The overall discordance rate was 5.3%. To calculate the sensitivity and specificity values, 2 × 2 contingency tables were constructed in two ways. In the first calculation, borderline histology was considered malignant, and the sensitivity and specificity rates were 97% and 92%, respectively. In the second analysis, it was accepted as benign, and these values were 100% and 98%, respectively. To determine the possible factors related with discordant diagnoses, age, menopausal status, tumoral size, laterality of tumors, and histologic diagnoses were analyzed. Significant association was noted for size and borderline and mucinous histologies. In patients with borderline histology, the discordance rate was 40%. This value for the remaining patients was 3.2% ( P < 0.001). The rate of misdiagnosis was 17.4% for mucinous tumors, whereas it was 4.8% for the remaining epithelial tumors ( P = 0.03). Frozen section evaluation revealed high sensitivity and specificity values in this study. To increase the accuracy of diagnosis, further diagnostic markers are needed especially for patients with large lesions, borderline tumors, and mucinous histologies.